2016
DOI: 10.1590/1414-431x20165373
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of modified platelet-rich plasma (mPRP) in promoting the proliferation and differentiation of dental pulp stem cells from deciduous teeth

Abstract: Stem cells from human exfoliated deciduous teeth (SHEDs) have great potential to treat various dental-related diseases in regenerative medicine. They are usually maintained with 10% fetal bovine serum (FBS) in vitro. Modified platelet-rich plasma (mPRP) would be a safe alternative to 10% FBS during SHEDs culture. Therefore, our study aimed to compare the proliferation and differentiation of SHEDs cultured in mPRP and FBS medium to explore an optimal concentration of mPRP for SHEDs maintenance. Platelets were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
2
18
0
Order By: Relevance
“…This is in agreement with other studies, which reported that higher concentrations (10%, 20%) of PRP induced significantly less proliferation compared to lower concentrations (2%, 5%) [59,60] possibly due to the inhibitory effect of prostaglandin E2 released by the platelet concentrate [61]. Two percent PRP seems to be the ideal concentration for the growth of exfoliated deciduous tooth MSCs [60]. The most surprising results in the current study were those of the 3-day cell proliferation assay.…”
Section:  Discussionsupporting
confidence: 93%
“…This is in agreement with other studies, which reported that higher concentrations (10%, 20%) of PRP induced significantly less proliferation compared to lower concentrations (2%, 5%) [59,60] possibly due to the inhibitory effect of prostaglandin E2 released by the platelet concentrate [61]. Two percent PRP seems to be the ideal concentration for the growth of exfoliated deciduous tooth MSCs [60]. The most surprising results in the current study were those of the 3-day cell proliferation assay.…”
Section:  Discussionsupporting
confidence: 93%
“…The cells outgrowing from the explants and the differentiation of DP-MSCs to three lineages in vitro are depicted in Figure 1 . In agreement with a recent report [ 9 ], we found extract of human platelets to be an optimal growth supplement for the expansion of DP-MSCs for clinical scale manufacturing. Additionally, DP-MSCs do not differ substantively from MSCs derived from adipose tissue, bone marrow, and umbilical cord tissue with regard to the internationally accepted vague criteria of plastic adherence and the ability to differentiate into osteoblasts, chondrocytes, and adipocytes in vitro while expressing mesenchymal (CD29, CD90, CD105, CD73, and CD44) but not hematopoietic lineage markers (CD14, CD34, and CD45) [ 10 ].…”
Section: Dental Pulp Mesenchymal Stem/stromal Cellssupporting
confidence: 93%
“…A few studies pointed out that PRP could improve odontogenic/osteogenic differentiation [13,34,35] and mineralization [11,12] of dental stem cells. PRP promoted mRNA and protein expression of DSPP and DMP-1 in SCAP [13].…”
Section: Discussionmentioning
confidence: 99%